Unravelling the depositional origins and diagenetic alteration of carbonate breccias - Madden, Robert; Wilson, M.; Mihaljevic, M.; Pandolfi, J.; Welsh, K. (Elsevier Science BV, 2017)
Abstract Carbonate breccias dissociated from their platform top counterparts are little studied despite their potential to reveal the nature of past shallow-water carbonate systems and the sequential alteration of such systems. A petrographic and stable isotopic study allowed evaluation of the sedimentological and diagenetic variability of the Cenozoic Batu Gading Limestone breccia of Borneo. Sixteen lithofacies representing six facies groups have been identified mainly from the breccia clasts on the basis of shared textural and compositional features. Clasts of the breccia are representative of shallow carbonate platform top and associated flank to basinal deposits. Dominant inputs are from rocky (karstic) shorelines or localised seagrass environments, coral patch reef and larger foraminiferal-rich deposits. Early, pre-brecciation alteration (including micritisation, rare dissolution of bioclasts, minor syntaxial overgrowth cementation, pervasive neomorphism and calcitisation of bioclasts and matrix) was mainly associated with marine fluids in a near surface to shallow burial environment. The final stages of pre-brecciation diagenesis include mechanical compaction and cementation of open porosity in a shallow to moderate depth burial environment. Post-brecciation diagenesis took place at increasingly moderate to deep burial depths under the influence of dominantly marine burial fluids. Extensive compaction, circum-clast dissolution seams and stylolites have resulted in a tightly fitted breccia fabric, with some development of fractures and calcite cements. A degree of facies-specific controls are evident for the pre-brecciation diagenesis. Pervasive mineralogical stabilisation and cementation have, however, led to a broad similarity of diagenetic features in the breccia clasts thereby effectively preserving depositional features of near-original platform top and margin environments. There is little intra-clast alteration overprint associated with subsequent clast reworking and post-brecciation diagenesis. The diagenetic-, and to an extent depositional- and clast-characteristics of the Batu Gading deposits are diagnostic of breccia origins. The predominance of: early and pervasive stabilisation of calcitic components, pervasive compaction resulting in a fitted texture, and paucity of meteoric dissolution or cementation effects are collectively all indicators of slope deposition and lithification. These features are comparable with other regional and global examples of submarine slope breccias, and in particular those also from syntectonic settings (Wannier, 2009). The results of this study, along with regional analogues, suggest the potential for reworked carbonate debris in slope settings to be a viable way of investigating carbonate platform variability and their subsequent alteration in the absence of preserved platform top or margin deposits.